Effectiveness of Ergonomic Training to Decrease Awkward Postures during Dental Scaling Procedures: A Randomized Clinical Trial - de Santana Sampaio Castilho, Ana Virginia (2021)
Studies demonstrate that there is a lack of effective ergonomic principles for adopting a neutral posture during the execution of dental procedures. ISO 11.226:2000 Standard, Corr. 1:2006 has been thoroughly evaluated and adapted to the way that dentists work by the European Society of Dental Ergonomics (ESDE). However, after 15 years, no studies that showed strong evidence of effectiveness in reducing the prevalence of awkward posture in applying its parameters within the scope of dental practice were found. The aim of this study was to verify the effectiveness of applying the ergonomic parameters proposed by the European Society of Dental Ergonomics (ESDE) and ISO 11226 in reducing the prevalence of the main awkward postures adopted by female dental surgeons during the execution of dental scaling on a dental mannequin. A randomized clinical trial was carried out with sixty dental surgeons randomly assigned to two groups: the intervention group, who received instructions and theoretical and practical ergonomic training; and the control group, who received the same training only at the end of the study. For data analysis, Software IBM SPSS 27 and RStudio was used. Descriptive statistics were performed to verify the effectiveness of the intervention, and generalized linear models (specifically, generalized estimated equation models) were used. Poisson distribution was carried out with log link function and network analyses. Sixty female dental surgeons participated in the study. Twenty-two were distributed in the intervention group and thirty-eight in the control group. It was found that ergonomic training enabled a 63% reduction in the prevalence of awkward postures and that there was a statistically significant difference (p < 0.001) only in the intervention group. The analyses showed that the estimated marginal means of postures not recommended in the groups' initial control, final control, initial intervention, and final intervention were 8.6, 8.2, 9.0, and 3.4, respectively. The relationship of networks analyses of the variables is shown with different profiles in the control and intervention groups, but the same pattern between the groups only vary in the strength and direction of the correlations. It was concluded that the ergonomic training based on the parameters of ISO 11226 and DIN EN 1005-4, and its adaptations to the dental practice provided by the European Society of Dental Ergonomics, as well as recent studies, contributed significantly to reducing the prevalence of awkward postures adopted by female dentists during the simulation of the basic periodontal procedures; however, it was not effective enough to improve the posture of the head and neck.